CHALLENGES TO EDUCATE THE MILLENNIAL MUSLIM GENERATION IN THE ERA OF THE INDUSTRIAL REVOLUTION 4.0 TO CREATE A MODERN ISLAMIC EDUCATION ENVIRONMENT - Suprima Suprima (Pusat Penerbitan Universitas (P2U) Unisba, 2022)
This research was conducted with the aim of knowing the challenges that exist in educating millennial Muslims in this era of development that is always changing, especially in the era of the industrial revolution 4.0 with the hope of creating a modern Islamic Education environment. This industrial revolution brings many positive opportunities in everyday life, but in reality there are millennials who are not able to deal with this well. Many millennials are deviating, be it a moral crisis and also a social crisis. This research is qualitative research with a literature study approach. Primary and secondary data sources used are obtained through literature study research by looking for books or writings relevant to this research. To educate the millennial Muslim generation in the era of revolution 4.0 by creating a modern Islamic education environment, to develop and implement Islamic Education in the environment must be a strong collaboration and become a shared responsibility, between the family environment, schools, communities, and also the existing government. This is done in the hope that it can be a guideline for millennials in utilizing developments that were originally a challenge and become opportunities that always lead to positive things.